REGENERASI TUNAS DARI KALUS YANG TELAH DIBERI PERLAKUAN IRADIASI PADA PADI VARIETAS FATMAWATI [Shoot Regeneration of the Fatmawati Rice Variant Radiated Callie] - Yunita, Rossa; Lestari, Endang G; Dewi, Iswari S (BERITA BIOLOGI, 2012)
Gamma ray mutative induction for increasing genetic variation has been applied for plant prime variety engineering. The materials are derrived from seed organ, shoot and calli. Calli is a group of actively dividing cell and have not been organized to form plant. The benefit of using calli explant is that the gamma ray could directly shot to DNA in the nuclear cell in such a way that there is higher opportunity for genetic change to occur. The problema of using calli explant are the difficulties in regenerating the calli into shoots, due to the deformation as a result of radiation process. Therefore, this research is aimed at obtaining the appropriate media formulation for shoot regeneration from Fatmawati-rice calli which has been irradiated with gamma ray. The reseach was conducted in BB-Biogen laboratory consisting of three experiments, such as : (1) calli iradiation with the dosage of 0; 5; 10; 15; 20; 25; 30; 35; 40; 45; 50; 55 and 60 Gy, (2) shoot regeneration at the MS + BA (0, 1, dan 3 mg/l) + IAA (0 dan 0,8 mg/l) media, and BA (0, 1, and 3 mg/l) + zeatin ( 0; 0,1; 0,2 and 0,3 mg/l) + IAA 0,8 mg/l and (3) Shoot induction at MS + IBA (0, 1, 2 and 3 mg/l) media. The result shows that the range of LD50 was obtained at the dosage of 30 Gy, the most apropriate media for shoot regeneration is MS + BA 3 mg/l + IAA 0,8 + zeatin 0,1 mg/l and media for root induction is IBA 1 mg/l.